Karakterisasi fisiologis dan biokimia penyebab penyakit bakteri pembuluh kayu pada tanaman cengkeh (Syzygium aromaticum L.) di PT Tirta Harapan - Mohammad Khoirul Amrulloh; Hardian Susilo Addy; Wiwiek Sri Wahyuni (Department of Plant Protection, Faculty of Agriculture, Universitas Jember - Indonesia, 2021)
Bacterial clove wood vessel disease is one of the diseases that affect clove production. The symptoms of the attack are characterized by yellowing of the leaves which then fall, branches and dead branches followed by sudden wilting with insect vectors namely Hindola sp. BPKC disease in 1990 was initially identified as Pseudomonas syzygii, but in 2004 it was re-identified as Ralstonia syzygii. The research method used is physiological characterization and biochemical characterization. The results of physiological characterization in the form of gram test, hypersensitivity test, NaCl level test and growth have the exact same character as the existing literature, while the results in biochemical characterization are glucose, sucrose, maltose, mannitol, dulsitol and sorbitol. only different in the dulsitol and sorbitol test. Keywords: characterization, bacterial wilt, identification